Digital Twin Testbed and Practical Applications in Production Logistics With Real-Time Location Data - Baalsrud Hauge, Jannicke; Zafarzadeh, Masoud; Jeong, Yongkuk; Li, Yi; Ali Khilji, Wajid; Larsen, Christian; Wiktorsson, Magnus (International Journal of Industrial Engineering and Management, 2021)
Nowadays, digital twins exist everywhere in various fields. However, an analysis of existing applications in manufacturing and logistics revealed that many entirely apply the concept. To identify when a complete implementation of the concept is beneficial, we analyse the need and the implications within production logistics. This study also presents an architecture supporting integrating a digital twin into production logistics and a corresponding application scenario. Based on this, we have derived practical applications. Each application is applied to different situations, and actual benefits can overcome the limitations of the previous studies. Article history: Received (January 16, 2021); Revised (May 13, 2021); Accepted (May 14, 2021); Published online (May 26, 2021)